Combined Alkali‐Organoammonium Structure Direction of High‐Charge‐Density Heteroatom‐Containing Aluminophosphate Molecular Sieves. Issue 27 (27th May 2019) - Seo, Seungwan; Ahn, Nak Ho; Lee, Jeong Hwan; Knight, Lisa M.; Moscoso, Jaime G.; Sinkler, Wharton A.; Prabhakar, Sesh; Nicholas, Christopher P.; Hong, Suk Bong; Lewis, Gregory J.
Abstract: The charge density mismatch concept was applied to the synthesis of high‐charge‐density silicoaluminophosphate SAPO‐69 (OFF) and SAPO‐79 (ERI) and zincoaluminophosphate PST‐16 (CGS), PST‐17 (BPH), PST‐19 (SBS), and ZnAPO‐88 (MER) molecular sieves. Combined alkali‐organoammonium structure direction in these systems is thus enabled. Structure direction is treated from the perspective of stabilizing an ionic framework, the relationships between reaction charge density (OH − /H3 PO4 ), alkali and organoammonium content, and ionicity of tetrahedral framework atoms in successful structure direction are presented. Abstract : The missing link : Introduction of combined alkali‐organoammonium structure direction allows access to high charge density ZnAPO and SAPO molecular sieves, including PST‐16 (CGS), PST‐17 (BPH), PST‐19 (SBS), ZnAPO‐88 (MER), SAPO‐69 (OFF), and SAPO‐79 (ERI).